Strategic Alliances: For Competition and Co-operation - Venkateshwarlu, M. (Indian Journal of Marketing, 2004)
Five year plans and other special development programs have had a positive impact on rural economy of India. Today, rural markets offer a vast untapped potential. Development programs in the fields of agriculture and allied activities, health, education, communication, rural electrification, etc have improved the life styles of rural population and a day may be imminent by which the quantum of rural demand may outweigh urban demand.To successfully exploit the potential of rural markets, and not to find but to make a rural market, there is a need to understand the vectors of rural markets not only in terms of households and population but also their occupational pattern, income generation, marketing arrangements for agricultural produce, the process of rural and cottage industrialization, communication facilities, rural buyer behavior, attitudes and beliefs of rural people and their aspirations.